Pengaruh Pendidikan Kesehatan Reproduksi Terhadap Pengetahuan Flour Albus pada Remaja Putri - Safira Delia Sandra Purwanti; Kristina Maharani; Qomariyah Qomariyah (Inovasi Kesehatan Global, 2025)
Flour Albus is one of the reproductive health problems commonly experienced by young women. Vaginal discharge is a condition of vaginal discharge other than blood that occurs outside of normal conditions, this fluid can be odorless or not, and is often accompanied by itching in the area around the vagina. The purpose of this study was to determine the effect of reproductive health education on knowledge of flour albus in young women. This type of research is quasi-experimental with a one-group pretest posttest design approach. The population taken was all 10th grade girls with a total of 40 respondents at SMK Theresiana Semarang. The sampling technique was total sampling. The data collection tool used a knowledge questionnaire. Data analysis used the Wilcoxon Test. The results of this study obtained a p-value of 0.002 (<0.05) which means there is an influence on reproductive health education on knowledge of flour albus in young women, with this Z-value of 3.052 which means that providing reproductive health education on flour albus has a 3-fold increase in knowledge in adolescents. Conclusion There is an influence on reproductive health education on knowledge of flour albus in young women. The suggestion that can be put forward is that young women can increase their understanding, awareness, knowledge and prevention methods because many young women still do not know the impacts and treatment and prevention of Flour Albus that occurs in themselves.